Book reviews 7.2 - Sandie Mourão; Jane Spiro (CLELEjournal, 2019)
Sandie Mourão reviews The Routledge Companion to Picturebooks, edited by Bettina Kümmerling-Meibauer (2017), which she finds to be an important starting point for any research into picturebooks. REVIEWER: SANDIE MOURÃO (UNIVERSIDADE NOVA, LISBON, PORTUGAL) Jane Spiro reviews Arting and Writing to Transform Education: An Integrated Approach for Culturally and Ecologically Responsive Pedagogy, by Meleanna Aluli Meyer, Mikilani Hayes Maeshiro and Anna Yoshie Sumida (2018), a book that she finds gives a unique pedagogical perspective with its deep connection to Hawaiian spirituality. REVIEWER: JANE SPIRO (OXFORD BROOKES UNIVERSITY, UK)